Children's Primary Dental Treatment Needs According to Their Parents - Gülsüm Duruk; Sibel Akküç; Zekiye Şeyma Gümüşboğa (Association of Support to Oral Health Research (APESB), 2021)
Objective: To determine the children's primary dental treatment needs reported by the parents and pediatric dentists. Material and Methods: 125 children (36 girls and 89 boys) and their parents participated in this study. The children's decayed-missing-filled teeth/teeth surfaces scores were recorded. A questionnaire about their children's primary dental treatment needs was conducted with the parents. Shapiro-Wilk test was used to test the normality of the data. Kruskal-Wallis test was used to compare the clinical findings according to the categorical variables. The Chi-Square test was used to compare the categorical data. Also, multiple linear regression analysis was performed to determine the effect of some variables on children's dmft/DMFT scores. The significance level was accepted as p<0.05. Results: The average age of the children who participated in the study was 7.59 ± 2.36 years. The main reason for applying to the paedodontics clinic was dental caries (38.4%), followed by dental pain (33.6%). As for the primary dental treatment needs, 28% of the parents said they needed dental filling, while 19.2% said they needed orthodontic treatment. According to the pediatric dentists, while the treatment rate of dental caries was 47.2% as the primary treatment need, it was only 4.8% for the orthodontic treatments. Conclusion: Turkish children who were admitted to paedodontics clinics were too old and dental caries and dental pain were the most common reasons for these visits to the clinics. The children's needs for primary treatment varied according to parents and pediatric dentists. There is a need for more comprehensive studies about the subject.